(untitled) (LIS TODAY, 2024)
This study explores the level of digital literacy among postgraduate and undergraduate students in different departments of Chandigarh University. With the increasing integration of digital tools and resources in education, it is essential to assess the proficiency of students in digital literacy skills, such as information literacy, internet literacy, ICT literacy, and media literacy. A survey method was employed, using a structured questionnaire to collect data from 110 students, selected through random sampling. The study analyzes the extent to which students are equipped with the necessary digital skills to navigate, evaluate, and effectively utilize online resources for academic and personal growth. The findings reveal that while a significant portion of students possess basic digital literacy awareness, there are gaps in advanced digital competencies. Additionally, the results highlight the growing importance of digital literacy in today’s academic environment and suggest that more targeted educational interventions are required to fully equip students with the skills necessary for success in a digitally-driven world. The study emphasizes the role of academic institutions in providing proper digital literacy training, ensuring that students are prepared to meet the demands of the evolving digital landscape. These insights will serve as a foundation for future research and policy development to enhance digital literacy education.